Ganong's review of medical physiology - Barrett, Kim E.; Barman, Susan M.,;Boitano, Scott,;Brooks, Heddwen L.,;Weitz, Michael,;Kearns, Brian Patrick,;Ganong, William F.,;Ganong, William F.; McGraw-Hill Education (Firm) (New York : McGraw Hill Education, 2016)
Thoroughly updated to reflect the latest research and developments in important areas, this text incorporates examples from clinical medicine to illustrate important physiologic concepts. Applauded for its interesting and engagingly written style, it concisely covers every important topic without sacrificing depth or readability
General principles & energy production in medical physiology -- Overview of cellular physiology in medical physiology -- Immunity, infection, & inflammation -- Excitable tissue: nerve -- Excitable tissue: muscle -- Synaptic & junctional transmission -- Neurotransmitters & neuromodulators -- Somatosensory neurotransmission: touch, pain, and temperature -- Vision -- Hearing & equilibrium -- Smell & taste -- Reflex and voluntary control of posture & movement -- Autonomic nervous system -- Electrical activity of the brain, sleep-wake states, & circadian rhythms -- Learning, memory, language & speech -- Basic concepts of endocrine regulation -- Hypothalamic regulation of hormonal functions -- The pituitary gland -- The thyroid gland -- The adrenal medulla & adrenal cortex -- Hormonal control of calcium & phosphate metabolism & the physiology of bone -- Reproductive development & function of the female reproductive system -- Function of the male reproductive system -- Endocrine functions of the pancreas & regulation of carbohydrate metabolism -- Overview of gastrointestinal function & regulation -- Digestion, absorption, & nutritional principles -- Gastrointestinal motility -- Transport & metabolic functions of the liver -- Origin of the heartbeat & the electrical activity of the heart -- The heart as a pump -- Blood as a circulatory fluid & the dynamics of blood & lymph flow -- Cardiovascular regulatory mechanisms -- Circulation through special regions -- Introduction to pulmonary structure & mechanics -- Gas transport & pH -- Regulation of respiration -- Renal function & micturition -- Regulation of extracellular fluid composition & volume -- Acidification of the urine & bicarbonate excretion
A Lange medical book.;This edition is a revision of the original works of Dr. Francis Ganong.--Preface
Includes bibliographical references and index
Keywords: Physiology -- Physiology